Silybin supplementation during HCV therapy with pegylated interferon-[alpha] plus ribavirin reduces depression and anxiety and increases work ability - Malaguarnera, Giulia; Be; Chisari, Giuseppe; Motta, Massimo; Vecchio, Michele; Vacante, Marco; Caraci, Filippo; Greco, Carmela; Drago, Filippo; Nunnari, Giuseppe; Malaguarnera, Michele (BMC psychiatry, 2016)
Background Hepatitis C virus infection and interferon treatment are often associated with anxiety, depressive symptoms and poor health-related quality of life. To evaluate the Silybin-vitamin E-phospholipids complex effect on work ability and whether health related factors (anxiety and depression) were associated with work ability in subjects with chronic hepatitis C treated with Pegylated-Interferon-[alpha]2b (Peg-IFN) and Ribavirin (RBV). Methods Thirty-one patients (Group A) with chronic hepatitis and other 31 subjects in Group B were recruited in a randomized, prospective, placebo controlled, double blind clinical trial. Group A received 1.5 mg/kg per week of Peg-IFN plus RBV and placebo, while Group B received the same dosage of Peg-IFN plus RBV plus association of Silybin 94 mg + vitamin E 30 mg + phospholipids 194 mg in pills for 12 months. All subjects underwent to laboratory exams and questionnaires to evaluate depression (Beck Depression Inventory - BDI), anxiety (State-trait anxiety inventory - STAI) and work ability (Work ability Index - WAI). Results The comparison between group A and group B showed significant differences after 6 months in ALT (P < 0.001), and viremia (P < 0.05), after 12 months in ALT (P < 0.001), and AST (P < 0.001), at follow up in AST (P < 0.05), and ALT (P < 0.001). Significant difference were observed after 1 month in WAI (p < 0.001) and BDI (P < 0.05), after 6 months in WAI (P < 0.05) and STAI (P < 0.05), after 12 months and at follow up in WAI, STAI and BDI (p < 0.01). Conclusions The supplementation with Silybin-vitamin E -phospholipids complex increased work ability and reduced depression and anxiety in patients treated with Peg-IFN and RBV. Trial registration NCT01957319, First received: September 25, 2013. Last updated: September 30, 2013 (retrospectively registered). Keywords: Silybin, Interferon, Hepatitis C, Depression, Anxiety, Work ability index